Educare alla pace: la sfida di un destino comune - Ceruti, Mauro (Studi sulla Formazione/Open Journal of Education, 2024)
Ernesto Balducci prophetically took up the challenge of a new Paideia, the Paideia of a planetary Humanism necessary to inhabit the complexity of a world in which everything is connected. A Paideia made necessary by the unprecedented possibility of human global self-destruction, produced by the simultaneous extraordinary increase in technological power and planetary interdependence.